2015
DOI: 10.4012/dmj.2014-215
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography for evaluation of enamel and protective coatings

Abstract: Optical coherence tomography (OCT) is an interferometric imaging technique. This study aimed to employ OCT to evaluate four different resin-based materials including a coating containing glass-ionomer filler and calcium, a giomer, and two fluoride-releasing self-etch resins. The coating and its underlying and adjacent enamel were monitored using swept-source OCT (center wavelength: 1330 nm) at baseline, after 5,000 thermal cycles, and after 1, 4 and 7 days of demineralization (pH 4.5). The coatings showed diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…This fact suggests that the effect of inhibition of demineralization of the S-PRG filler containing experimental pastes was not only due to F ions, but also related to other ions released from the S-PRG fillers 32) . A recent study on a S-PRG containing coating material also suggested that multiple ions release from these fillers increased the resistance of enamel against demineralization 33) . It was shown that ions released from the S-PRG filler had antibacterial and pH neutralizing effects on acidic solutions [34][35][36] .…”
Section: Discussionmentioning
confidence: 95%
“…This fact suggests that the effect of inhibition of demineralization of the S-PRG filler containing experimental pastes was not only due to F ions, but also related to other ions released from the S-PRG fillers 32) . A recent study on a S-PRG containing coating material also suggested that multiple ions release from these fillers increased the resistance of enamel against demineralization 33) . It was shown that ions released from the S-PRG filler had antibacterial and pH neutralizing effects on acidic solutions [34][35][36] .…”
Section: Discussionmentioning
confidence: 95%
“…The axial and lateral optical resolutions in air were 12 and 20 µm, respectively. The details of this system have been described elsewhere 16,17) . The specimens were washed with deionized water under controlled hydrated conditions at each scanning time-point.…”
Section: Optical Assessment Of Demineralization By Oct Imaging and Qumentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a newly developed, non-invasive, cross-sectional, real-time Comparison of resin-based and glass ionomer sealants with regard to fluoriderelease and anti-demineralization efficacy on adjacent unsealed enamel imaging tool that has been widely used for the nondestructive assessment of enamel and dentine demineralization, as well as the interfacial adaptation of sealant and restorative materials 16,17) . Quantitative measurement of light propagation in tissues, measured as the attenuation coefficient (µ t) parameter in OCT, has shown promising results with regard to its ability to discriminate between sound and demineralized tooth structures [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been introduced as the true hybridization of glass ionomer (GI) and composite resin and has the distinguishing feature of a stable surface prereacted glass ionomer (S-PRG), which is coated with an ionomer lining incorporated in a resin matrix. This arrangement aids in the protection of the glass core from moisture, adding to long-standing aesthetics, durability, physical and handling properties of composite resins with fluoride release, and recharge property like the GI cement [15]. …”
Section: Introductionmentioning
confidence: 99%